2011
DOI: 10.1253/circj.cj-10-0647
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Acute Gain on Clinical Outcomes of Patients Treated With Sirolimus-Eluting Stent - A Sub-Analysis Study From the STLLR Trial -

Abstract: Background: Geographical miss (GM), representing suboptimal drug-eluting stent deployment, is associated with an increased risk of target lesion revascularization (TLR) and myocardial infarction. The impact of suboptimal stenting techniques on clinical outcomes in diabetics remains unknown. Methods and Results:Stent deployment Techniques on cLinicaL outcomes of patients treated with the cypheR TM stent (STLLR) is the first multicenter, large trial to prospectively evaluate outcomes associated with sirolimus-el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 25 publications
(14 reference statements)
1
8
0
Order By: Relevance
“…Longitudinal geographic miss (LGM) is the failure to fully cover a diseased coronary segment during percutaneous coronary intervention (PCI) procedures. The Stent deployment Techniques on clinical outcomes of patients treated with the cypher stent trial (STLLR) prospectively evaluated the impact of stent deployment technique in manual PCI (M‐PCI) on outcomes, and established a direct correlation between the occurrence of LGM and the resulting negative impact on long‐term clinical outcomes when compared with patients without LGM . Patients with LGM at 12 months post PCI in the STLLR trial had significantly higher incidences of target vessel revascularization (TVR) (6.1% vs 2.6%; P < 0.05) and myocardial infarction (MI) (2.4% vs 0.8%; P = 0.04) than patients without LGM.…”
Section: Introductionmentioning
confidence: 99%
“…Longitudinal geographic miss (LGM) is the failure to fully cover a diseased coronary segment during percutaneous coronary intervention (PCI) procedures. The Stent deployment Techniques on clinical outcomes of patients treated with the cypher stent trial (STLLR) prospectively evaluated the impact of stent deployment technique in manual PCI (M‐PCI) on outcomes, and established a direct correlation between the occurrence of LGM and the resulting negative impact on long‐term clinical outcomes when compared with patients without LGM . Patients with LGM at 12 months post PCI in the STLLR trial had significantly higher incidences of target vessel revascularization (TVR) (6.1% vs 2.6%; P < 0.05) and myocardial infarction (MI) (2.4% vs 0.8%; P = 0.04) than patients without LGM.…”
Section: Introductionmentioning
confidence: 99%
“…The procedure involves advancement of yet another catheter and accurate placement of the NC balloon within the borders of the stent is not always achieved and this may result in edge dissection, geographic miss [21], or even coronary perforation [22]. These complications typically lead to additional stenting or target lesion revascularization at a later stage.…”
Section: Discussionmentioning
confidence: 99%
“…While it has been clearly demonstrated that high-pressure postdilatation with the NC balloon helps optimise stent expansion and achieve a large lumen, disadvantages to the approach may also exist. Aggressive post-dilatation might result in more intimal hyperplasia compared with a less aggressive approach, 19 or lead to edge dissections, geographic miss 20 or even coronary perforation. 21 These complications may require additional stenting and influence TLR adversely.…”
Section: Disadvantages Of Nc High-pressure Post-dilationmentioning
confidence: 99%